CARDIOVASCULAR COMPLICATIONS OF ANTITUMOR THERAPY FOR BREAST CANCER: DIAGNOSIS, PREVENTION AND TREATMENT - V. I. Potievskaya; A. A. Akhobekov; L. V. Bolotina; L. A. Koroleva; A. D. Kaprin (Сибирский онкологический журнал, 2021)
Although significant advances have been made in breast cancer treatment resulting in improved survival, cardiovascular disease has become the main cause of disability and mortality not related to cancer recurrence. In the general population, cardiovascular disease is the leading cause of death in both women and men. In patients with breast cancer, the incidence of cardiovascular diseases is even higher than in the general population. The high incidence of cardiovascular disease in breast cancer patients is likely due to the presence of common risk factors as well as the patients with breast cancer, the incidence of cardiovascular diseases is even higher than in the general population. The high incidence of cardiovascular disease in breast cancer patients is likely due to the presence of common risk factors as well as cardiotoxicity of anticancer therapy. The rise in the development of cardiovascular disease in breast cancer survivors is a major concern. This literature review will describe the incidence of cardiovascular complications with different treatment regimens for breast cancer, risk factors for their development, strategies for monitoring cardiovascular function during and after anticancer therapy, and strategies for the prevention and treatment of cardiotoxicity.